2020
DOI: 10.1055/s-0040-1718890
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Bone Remodeling Disorder in Hemophilia

Abstract: Hemophilia is caused by a lack of antihemophilic factor(s), for example, factor VIII (FVIII; hemophilia A) and factor IX (FIX; hemophilia B). Low bone mass is widely reported in epidemiological studies of hemophilia, and patients with hemophilia are at an increased risk of fracture. The detailed etiology of bone homeostasis imbalance in hemophilia is unclear. Clinical and experimental studies show that FVIII and FIX are involved in bone remodeling. However, it is likely that antihemophilic factors affect bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 111 publications
0
14
0
1
Order By: Relevance
“…The molecular mechanisms of FVIII or FIX deficiency leading to osteoporosis have been explored. Studies have shown that the RANK/RANKL/OPG signaling pathway plays a role in the development of osteoporosis in PWH [ 6 , 20 , 21 ]. Receptor activator of nuclear factor kappa-B ligand (RANKL) binds to its receptor, RANK, and promotes osteoclastogenesis, resulting in increased bone resorption [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular mechanisms of FVIII or FIX deficiency leading to osteoporosis have been explored. Studies have shown that the RANK/RANKL/OPG signaling pathway plays a role in the development of osteoporosis in PWH [ 6 , 20 , 21 ]. Receptor activator of nuclear factor kappa-B ligand (RANKL) binds to its receptor, RANK, and promotes osteoclastogenesis, resulting in increased bone resorption [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, thrombin influences bone metabolism mainly by altering the expression of cytokines [ 20 ]. Thrombin is involved in the metabolism of arachidonic acid by binding to PAR-1 on the osteoblast membrane [ 6 ]. PAR-1 stimulates the expression of cyclooxygenase-2 (COX-2) through the mitogen-activated protein kinase (MAPK) pathway [ 39 ], and upregulated COX-2 catalyzes the conversion of arachidonic acid to prostaglandin E2 (PGE2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism leading to reduced BMD is unclear, although it is likely multifactorial. Deficiencies in coagulation factors and reduced mobility due to haemophilic arthropathy and target joints have been suggested to contribute to reduced BMD 7 …”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies in coagulation factors and reduced mobility due to haemophilic arthropathy and target joints have been suggested to contribute to reduced BMD. 7 Factor (F)VIII prophylaxis has long been the standard of care for PwHA without FVIII inhibitors. 8 However, despite improvements in trough factor level and improved bleed control, 9 subclinical joint bleeding can still lead to debilitating joint damage.…”
Section: Introductionmentioning
confidence: 99%